Identification and assessment of cases of malignant hyperthermia triggering under anaesthetic management: analysis of spontaneous reporting database - E. Yu. Kolesnikova; E. O. Zhuravleva; I. L. Asetskaya; K. E. Zatolochina (Безопасность и риск фармакотерапии, 2018)
The article provides analysis of the Federal adverse drug reaction database for the period 2009-2014 years, whose goal was to identify and assess cases of malignant hyperthermia after exposure to inhalational anaesthetics. During this time were identified 10 reports satisfying these requirements.